Enhanced Stability of Long-Living Immobilized Recombinant β-d-N-Acetyl-Hexosaminidase A on Polylactic Acid (PLA) Films for Potential Biomedical Applications - Eleonora Calzoni; Alessio Cesaretti; Nicolò Montegiove; Alessandro Di Michele; Carla Emiliani (Journal of Functional Biomaterials, 2021)
β-d-N-acetyl-hexosaminidase (Hex, EC 3.2.1.52) is an acid hydrolase that catalyzes the cleavage of the β-1,4 bond in N-acetyl-d-galactosamine (Gal-NAc) and N-acetyl-d-glucosamine (Glc-NAc) from the non-reducing end of oligosaccharides and glycoconjugates. It is widely expressed in both the prokaryotic and eukaryotic world, where it performs multiple and important functions. Hex has antifungal activity in plants, is capable of degrading many biological substrates, and can play an important role in the biomedical field for the treatment of Tay-Sachs and Sandhoff diseases. With the aim being able to obtain a device with a stable enzyme, a method of covalent immobilization on polylactic acid (PLA) films was developed for the A isoform of the β-d-N-acetyl-hexosaminidase enzyme (HexA), produced in a recombinant way from Human Embryonic Kidney-293 (HEK-293) cells and suitably purified. An in-depth biochemical characterization of the immobilized enzyme was carried out, evaluating the optimal temperature, thermal stability, pH parameters, and Km value. Moreover, the stability of the enzymatic activity over time was assessed. The results obtained showed an improvement in terms of kinetic parameters and stability to heat for the enzyme following immobilization and the presence of HexA in two distinct immobilized forms, with an unexpected ability for one of them to maintain its functionality for a long period of time (over a year). The stability and functionality of the enzyme in its immobilized form are therefore extremely promising for potential biotechnological and biomedical applications.